2015
DOI: 10.1108/jfmm-07-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

The development of an apparel industry business model for Canada

Abstract: Purpose – Earlier attempts to develop a strategy for the apparel industry in Canada to counter the adverse effects of trade liberalisation on Canadian apparel suppliers have been based on the concept of clustering. However, despite the support from government-supported industry bodies, clustering has not been forthcoming and this situation has created a pressing need for the development of an alternative to the clustering strategy. A study by the Canadian Apparel Human Resources Council offered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…However, the main factors that lead consumers to engage in more sustainable methods of transportation are economic, as consumers realize that they can spend considerably less money and time by giving up ownership of their car(s). Even though previous research has found that “women … behave in more environment‐friendly ways than men” (Campaniaris, Murray, Hayes, & Jeffrey, , p. 154), we found no differences in the sample regarding gender, as the main reason mentioned by both male and female subjects for car disposal was financial. This aspect of non‐specific demographic characteristics in the process of disposal is consistent with the findings from Lindblom and Lindblom (); in a study conducted in Finland, in 2010, during an economic crisis, they showed that de‐ownership orientation was evenly spread across socio‐demographic groups.…”
Section: Discussioncontrasting
confidence: 97%
“…However, the main factors that lead consumers to engage in more sustainable methods of transportation are economic, as consumers realize that they can spend considerably less money and time by giving up ownership of their car(s). Even though previous research has found that “women … behave in more environment‐friendly ways than men” (Campaniaris, Murray, Hayes, & Jeffrey, , p. 154), we found no differences in the sample regarding gender, as the main reason mentioned by both male and female subjects for car disposal was financial. This aspect of non‐specific demographic characteristics in the process of disposal is consistent with the findings from Lindblom and Lindblom (); in a study conducted in Finland, in 2010, during an economic crisis, they showed that de‐ownership orientation was evenly spread across socio‐demographic groups.…”
Section: Discussioncontrasting
confidence: 97%
“…Gandhi (2012) illustrates the point that PLM approaches are not restricted to engineering through reference to the emerging applications of PLM in the retail sector. Many authors (d'Avolio et al , 2015; Campaniaris et al , 2015; Segonds et al , 2015; Vezzetti et al , 2017) describe the fashion and textiles sector as a late adopter of PLM in comparison to other manufacturing industries where PLM is well known and well-established. The need for more widespread information within the apparel sector is revealed by Easters (2012b) who suggests the extensive terminologies or acronyms are becoming “lost in translation” with PDM being poorly understood and PLM simply viewed as the renaming of PDM.…”
Section: Findings: Descriptive Analysismentioning
confidence: 99%
“…Where PLM is implemented it appears that organisations are now focusing on new product development (d'Avolio et al , 2015; Bandinelli et al , 2013; Segonds et al , 2015 and Vezzetti et al , 2017). Whereas, a holistic, ambitious, collaborative strategic vision for the apparel sector in Canada is presented by Campaniaris et al (2015). Wixom et al (2013) show how connecting business silos to users can support optimal decision making.…”
Section: Findings: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations